Qualidade da informação de mortalidade por causas externas em Fortaleza-CE (2017-2020): análise de códigos garbage - Moura, Lydia Meneses de (2023)
The registration of deaths from external causes of a population is the essential source of basic health and safety information. In view of this, mortality surveillance has been increased in order to increase the integrity and quality of the event notification record in the SIM. However, the quality of statistics on causes of death has been questioned, as around 400,000 deaths/year are registered in the SIM with causes classified as garbage codes (GC). Deaths due to GC represent an indicator of the quality of health care, as inequality in access and quality of medical care are results related to the proportion of deaths due to ill-defined causes. Therefore, the objective is to analyze the quality of information on mortality from external causes in Fortaleza-CE between 2017 and 2020. This is a ecological and cross-sectional, descriptive study, with a quantitative approach of secondary data from the information on mortality from external causes available. in the Fortaleza SMS database. The analysis was carried out by ANACONDA, a tool that identifies problems that need to be investigated in order to improve the quality of data on mortality, guiding health policies and actions. The ANACONDA analysis consists of 10 steps, grouped into four broad categories: Overview of data and initial checks; Mortality data; Data on causes of death; and Overall data quality index. For the analysis, the following variables were used: sex, age group, GC categories, garbage levels, causes of mortality from external causes, considering chapter XX of the ICD-10. The project was approved by CEP/PPGSP-UFC via opinion 5.772.791. The findings showed that the quality of information on mortality from external causes in Fortaleza-CE is deficient, as there is an increase in the percentage of less useful causes from 2017 to 2020, with a high level of severity as the most prevalent, over the course of of years (from 68% to 89,5%%%). Despite the death profile being similar to other studies, homicides in men aged 15 to 29, we identified in virtually all ranks the ICD-10 code Y34.9 (refers to Unspecified facts or events and undetermined intent), reinforcing the need to improve the quality of information by reducing GC. The temporal evolution of the VSPI-Q proved to be very low in all years (from 17% to 10,2%%%), which reinforces the need for more effective measures for coverage in the notification and detailing of the causes, scores that most interfered in the result of this index.